Brazil: managing water quality : mainstreaming the environment in the water sector - Margulis, Sergio; Hughes, Gordon; Gambrill, Martin; Azevedo, Luiz Gabriel T. (World bank technical paper. Environment, 2002)
Introduction - Water resources management - Water supply and sanitation - Environmental management in the water sector - An integrated approach to water quality - Annex.